(untitled) (EAAE Annual Conference Proceedings, 2023)
EAAE aims to ensure the education and empowerment of the future generations of architects, designers and planners – leading to careers as socially responsible, culturally engaged creative citizens.In its quest for building an inclusive and sustainable future, also the New European Bauhaus initiative relies on empowered and educated citizens.